Espa??os de educa????o libertadora: a dissidente voz de uma escola suficientemente boa - Scardua, Martha Paiva (2016)
Since 2013, a social, political and economic crisis that unveils a brutal esthetics of ways of being and acting has been consolidated in Brazil. The pressures for neoliberal and conservative policies that set aside democracy in the country are being manifested in Education, putting the struggle for rights that have already been guaranteed back on the agenda. In addition to the struggle against privatization, one can add the fight against the managerialism of schools and learning, the scaling down of teaching to elementary contents, the fight for the permanence of dialogic processes in the educational act, the freedom of expression and the teaching of life???s curriculum. By understanding the school???s role to provide the tools for the ethical and critical confrontation of problems, this research sought to identify and explore the concepts and principles of a liberating education in practices carried out in the Federal District???s network of public schools, and to point to possible alternative paths. Guided by the dialogic, liberating education (Freire), ethics of liberation (Dussel) and analectic methods, we carried out, initially, a theoretical bibliographic research in a good enough school (GES), with contributions from Winnicott, Arendt, Biesta, Mignolo and Smith. The multiple case studies investigated 33 pedagogical practices of teachers, guidance counselors, pedagogic coordinators, school managers, students and a psychologist. The semi-structured interviews and rounds of conversation that were carried out enabled us to have a more profound understanding of liberating acts of Education, as well as to have the criticism and contribution of participants in the theoretical construct of the research. The final data analysis was guided by the Theory Based on Data and revealed that the investigated practices are guided by ethical, democratic, pedagogic and methodological principles that dialogue with pedagogic, democratic, critical and liberating trends. It also demonstrated that the differential in the participants??? practices is expressed through loveliness and the capacity to believe in, be with and do with. At the end, the study presented a synthesized concept of liberating education that aggregated the participants??? discourses and contributed with a redefinition of the concept of liberating education in a GES, which questions the function of the school in the face of local, national and global problems. The study indicated that schools must find a balance between the educational dimensions of qualification (know-how), democratization (know-how to coexist), humanization (know-how to be) and transcendentalism (know-how to care), and to promote potential spaces of appearance that involve listening, accepting and caring for the students, and the exercise of global citizenship at school. The problematizations here presented point to the transformation of the school in a space for the production and dissemination of culture and knowledge, which can promote the decolonization and liberation from careless ways of being and acting in the world, and a relationship with reality and the Other, based on believing in, being with and doing with.